Investigation the effect of weathering on chemically strengthened flat glasses - Gosterislioglu, Y. A.; Ersundu, A. E.; Ersundu, M. Celikbilek; Sokmen, I (ELSEVIER, 2020)
Present work discusses weathering behavior of chemically strengthened flat glasses. With this aim, different soda-lime silicate and sodium aluminosilicate glasses were subjected to weathering tests before and after chemical strengthening to simulate possible scenarios that toughened glass products face and effect of weathering on topographical, optical, structural and mechanical properties were investigated. Topographical evaluations were made through roughness measurements and topography images using white light interferometery and atomic force microscopy techniques. Depth profiling was accomplished by time of flight secondary ion mass spectroscopy. Optical transmittance spectra were recorded with ultraviolet-visible-near infrared spectrophotometer. Structural properties were analzyed by Fourier-transform infrared spectroscopy. Mechanical testing was realized by applying biaxial bending and Vickers indentation tests. Experimental results revealed that soda-lime silicate glasses are more prone to corrosion when weathering takes place after chemical strengthening due to formation of alteration layers. This behavior can be altered by increasing alumina content in the glass composition.
Keywords: Chemical strengthening; Flat glass; Weathering; Alteration layer; Glass composition; ION-EXCHANGE; SILICA GLASS; STRESS-CORROSION; FLOAT GLASS; VICKERS INDENTATION; SURFACE; WATER; SPECTROSCOPY; TEMPERATURE; MECHANISMS; Materials Science